Studies of Expression of Peptaibol Synthetase of Trichoderma reesei - Irinyi, László; Sándor, Erzsébet; Kövics, György (Acta Agraria Debreceniensis, 2005)
Because of the potential importance of peptaibols in the biological control of plant diseases, a transgenic, a T. reesei strain carrying a tex1-promoter: goxA fusion plasmid was constructed for furthur studies. The peptaibol synthetase gene (which is highly similar to T. virens tex1) was identified in the genome sequence of T. reesei. A 900 bp 5’ upstream noncoding fragment, presumed to include the promoter region of tex1, was cloned into the pSJ3 plasmid (which contains the Aspergillus niger goxA gene encoding glucose oxidase). Finally, we transformed T. reesei with the tex1-promoter: goxA fusion containing pSJ3 plasmid.